Relationship between Money Supply, Income and Price Level in Nepal - Achary, Ram Chandra (NRB Economic Review, 2019)
Using the data from 1974/75 to 2017/18, this paper intended to find out the relationship between money supply, income and price level in Nepal. The paper has established the relationship between real money supply (both M1 and M2) with respect to real GDP, nominal money supply (both M1 and M2) with respect to price level and nominal GDP with respect to price level separately. The econometric tools such as ADF for unit root tests, SIC for lag length selection, bivariate Johansen Cointegration tests followed by VECM has been used for long-run causality. Further, VEC as well as VAR Granger Causality/Block Exogeneity Wald tests for short-run causality are used. The paper found bidirectional longrun causality between the real income with respect to both type of money supply in real terms. But there is no evidence of short run causation between these variables. Likewise, the study found the unidirectional long-run relationship runs from narrow money supply to consumer price. However, there is no short-run relationship from either side. Accordingly, there is no evidence of long-run as well as short-run relationship between broad money supply and consumer price level. Lastly, there is no evidence of long-run causality between nominal GDP and general price level. But the study found unidirectional short-run causality running from general price to nominal GDP. The results suggest that Nepal should focus on growth of time deposit component of broad money supply in long-run for economic growth and control of inflation.